The importance of English in multinational companies in Bangladesh: Corporate expectation vs reality - Shahriar, Md. Abid Hasan (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.